Can peace research make peace? lessons in academic diplomacy - Kivimaki, Timo (International relations monographs, 2012)
This book is about the process and, more generally, about the opportunities that peace research and the teaching of conflict resolution can offer academic diplomacy. As such the book is both an empirical and a theoretical project. While it aims at being the most comprehensive analysis of the conflict in West Kalimantan.